Lycopene and prostate cancer: an overview - Carini, Francesco; Zeenny, Marie Noel; Di Trapani, Benedetto; Palumbo, Vincenzo; Geagea Gerges, Alice; Sinagra, Emanuele; Leone, Angelo; Tomasello, Giovanni (Progress in Nutrition, 2018)
Prostate cancer is one of the most common cancers in the world. Its pathogenesis is multifactorial and is linked to risk factors such as age, diet, cigarette smoking, family history and the onset of oxidative stress. In recent times, therefore, we are investigating the use of antioxidants as primary and tertiary prevention of prostate cancer. Numerous studies in the literature focused on lycopene, a molecule belonging to the family of carotenoids that is commonly found in tomatoes and products derived from it. The literature analyzed in the last two years shows how lycopene inhibits different mechanisms linked to carcinogenesis and tumor progression. However, there are still many points to be clarified the real antitumoral capacity of this substance.